Changes in Clinical Measures and Tissue Adaptations in Collegiate Swimmers Across a Competitive Season - Paul, Ryan William; Tate, Angela; Sarver, Joseph; DiPaola, Laura; Yim, Jeffery; Thomas, Stephen John (CommonHealth, 2020)
Background: Due to high training volume, competitive swimmers incur shoulder pain and injury1, but certain physical characteristics, such as shoulder ROM and endurance, and tissue adaptations such as posterior capsule thickness (PCT) and supraspinatus tendon structure may also be risk factors. Decreased endurance and ROM have been found in competitive swimmers along with being related to pain2. However, no longitudinal studies have examined pain and disability, range of motion, training volume, shoulder endurance and tendon structure over the course of a competitive season. Purpose: The purpose of this study was to: 1) to assess shoulder pain and disability, internal rotation (IR) and external rotation (ER) and horizontal adduction (HADD) ROM, and posterior shoulder endurance longitudinally over a competitive collegiate season, and 2) determine if there is a relationship between swimming yardage, supraspinatus tendon organization and posterior capsule thickness. Methods: 17 male and 13 female Division III swimmers aged 19.6 ± 1.1 years participated. Pain and disability were assessed using the Penn Shoulder Score and the Disability of Arm Shoulder Hand sports module. Internal rotation (IR), external rotation (ER), and horizontal adduction (HA) were measured using a digital inclinometer. Shoulder endurance was measured using the Posterior Shoulder Endurance Test (PSET). Anterior, center, and posterior supraspinatus tendon images were collected by locating the anterior aspect of the tendon insertion and moving posteriorly. The ultrasound images were analyzed using custom MATlab software to quantify tissue organization. All measures were found in the beginning (T1), middle (T2), and end (T3) of the season. Repeated measure ANOVAs were used to compare longitudinal changes across time. If p-values were found to be ≤ 0.05, follow-up paired t-tests with Bonferroni corrections were used to compare T1, T2, and T3. This protocol was IRB-approved and participants signed a written consent form. Results: An increase in swimming yardage from T1 to T2 was followed by a significant decrease in yardage to finish the swimming season (Table 1). Disability decreased and endurance increased throughout the season with no observed changes in pain. IR and HA ROM decreased significantly between all timepoint comparisons. Tendon banding frequency did not change over time (Table 2). Discussion: Large amounts of IR during the pull phase and late initiation of ER during the recovery phase have been associated with a high risk of impingement4. The relationship between pain, disability, and range of motion may suggest that a reduction of IR could protect the swimmers’ shoulder by limiting impingement through the pull and recovery phases. However, further investigation is required to confirm. The lack of statistical significance longitudinally in tendon organization is not surprising since there were no changes in pain, a decrease in disability, and an increase in endurance. Conclusion/Clinical Relevance: Further research is required to understand the relationship between training volume, tendon organization, and disability. Collegiate swimmers demonstrate increased endurance and decreased disability over the course of the season. It may suggest that the loss of ROM is a positive adaptation and may be protective.